Positioning of Store Brands - Sayman, Serdar; Hoch, Stephen J.; Raju, Jagmohan S. (Marketing Science, 2002)
We examine the retailer's store brand positioning problem. Our game-theoretic model helps us identify a set of conditions under which the optimal strategy for the retailer is to position the store brand as close as possible to the stronger national brand. In three empirical studies, we examined whether market data are consistent with some of the implications of our model. In the first study, using observational data from two US supermarket chains, we found that store brands are more likely to target stronger national brands. Our second study estimated cross-price effects in 19 product categories, and found that only in categories with high-quality store brands, store brand and the leading national brand compete more intensely with each other than with the secondary national brand. In a third product perception study, we found that although explicit targeting by store brands influenced consumer perceptions of physical similarity, it had no influence on consumers' perceptions of overall or product quality similarity. While it appears that retailers do follow a positioning strategy consistent with our model, it changes buying behavior in the intended fashion only if the store brand offers quality comparable to the leading national brands.